2003
DOI: 10.1002/jnr.10732
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between NMDA receptor expression and MPP+ toxicity in cultured dopaminergic cells

Abstract: It has been suggested that excitotoxicity could be contributing to dopamine cell loss after methylphenylpyridinium ion (MPP+) exposure, although the literature regarding this is contradictory. Given that in cell culture excitotoxicity has been reported to be dependent on culture age, we postulated that these discrepant results might be explained by a difference in developmental expression of N-methyl-D-aspartate (NMDA) receptors. To test this, mesencephalic cells were cultured and the number of dopaminergic ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…One possibility for this discrepancy could be a result of differences in expression levels of NMDA or TNF␣ receptors. We and others have observed that expression of NMDA and TNF␣ receptors is dependent on culture age, culture density, and the presence of contaminating glia (Daniels and Brown, 2001;Church and Hewett, 2003) (data not shown). Previous culture protocols contained an apparently higher number of glia than ours, and the culture age and neuronal plating density used also differ (Houzen et al, 1997;Furukawa and Mattson, 1998).…”
Section: Discussionmentioning
confidence: 61%
“…One possibility for this discrepancy could be a result of differences in expression levels of NMDA or TNF␣ receptors. We and others have observed that expression of NMDA and TNF␣ receptors is dependent on culture age, culture density, and the presence of contaminating glia (Daniels and Brown, 2001;Church and Hewett, 2003) (data not shown). Previous culture protocols contained an apparently higher number of glia than ours, and the culture age and neuronal plating density used also differ (Houzen et al, 1997;Furukawa and Mattson, 1998).…”
Section: Discussionmentioning
confidence: 61%
“…2003). In this model, the contribution of NMDA‐receptor mediated mechanism increases with increasing MPP + doses (Church and Hewett 2003), and glutamate toxicity through these receptors is exacerbated by low doses of MPP + (Sawada et al. 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the here‐described mouse VM cultures, the toxicity of MPP + decreased with time in vitro . This is in line with other in vitro studies using primary mesencephalic (Church & Hewett, 2003; Danias et al ., 1989; Koutsilieri et al ., 1995) or sympathetic cell cultures (Bhave et al ., 1996). This may seem in contrast to the in vivo situation, where vulnerability for MPTP increases with ageing (Irwin et al ., 1993; Desai et al ., 1996; Sugama et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%